(untitled) (Research, Society and Development, 2022)
Introduction: Violence is considered a phenomenon that lasts for centuries in society. The high incidence of cases of violence during childhood and adolescence draws attention nationally and worldwide. The aim of this study is to analyze the epidemiological situation of sexual violence in childhood in the state of Alagoas from 2009 to 2019. Methodology: This is an epidemiological, quantitative, descriptive and documentary research. The time range adopted comprises the period from 2009 to 2019, using the variables "age group", "sex of victims", "place of occurrence of violence", "repeated violence", type of aggressor "unknown", "municipalities of occurrence" and "year". Results and Discussion: Most of the violence occurred inside homes; the perpetrators are people intimately known to the victims and their families. The problem of preparation, knowledge of professionals, structure of support network, fear and lack of protection of the professional author of the notification before the legal processes, the performance of the Tutelary Councils is precarious, the lack of training, in addition to activities, considered by nurses, of greater relevance, influence the underreporting of cases. Final considerations: It was identified that compulsory notification should be understood as one of the main stages for coping with child violence, because these epidemiological data should be used to plan interventions to cope with violence. It is important to problematize the data available in order to plan interventions, such as preventive and educational actions, contributing to a decrease in cases of child violence. Such actions precede the act of violation of the child’s rights and dignity generated by the abuse.